2015
DOI: 10.1002/joc.4379
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution climate simulations with COSMO‐CLM over Italy: performance evaluation and climate projections for the 21st century

Abstract: This study presents the results of dynamically downscaled climate simulations over Italy produced with the COSMO-CLM model. Three simulations forced by ERA-Interim Reanalysis were conducted respectively at a spatial resolution of 0.22 ∘ , 0.125 ∘ and 0.0715 ∘ over the period 1979-2011. The results were analysed in terms of 2-m temperature and precipitation with the aim of assessing the model's ability to reproduce these important features of the Italian climate. The results were validated by comparing model ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
90
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 65 publications
(82 reference statements)
16
90
0
Order By: Relevance
“…The simulations have been deeply analysed in Bucchignani et al (2015) and -in terms of extreme events -in Zollo et al (2015a), showing a general good agreement with observed data. Furthermore, as explained in Bucchignani et al (2015), the results of these simulations are consistent, in terms of both mean bias and projections, with those obtained from the EURO-CORDEX ensemble data (Giorgi et al, 2009), which represent the 'state-of-the-art' of regional climate simulations over Europe at 0.11°of horizontal resolution.…”
Section: Climate Simulationssupporting
confidence: 69%
See 1 more Smart Citation
“…The simulations have been deeply analysed in Bucchignani et al (2015) and -in terms of extreme events -in Zollo et al (2015a), showing a general good agreement with observed data. Furthermore, as explained in Bucchignani et al (2015), the results of these simulations are consistent, in terms of both mean bias and projections, with those obtained from the EURO-CORDEX ensemble data (Giorgi et al, 2009), which represent the 'state-of-the-art' of regional climate simulations over Europe at 0.11°of horizontal resolution.…”
Section: Climate Simulationssupporting
confidence: 69%
“…The main features of the model and of its setup are reported in Bucchignani et al (2015) and are briefly recalled in Table 1. Simulations were performed over Italy, employing a spatial resolution of 0.0715°(about 8 km).…”
Section: Climate Simulationsmentioning
confidence: 99%
“…The good capabilities of the model in reproducing PDFs observed in the present work, combined with the finding of several literature works (e.g., [33,37]) confirm that, especially in some complex areas, high-resolution simulations could provide good improvements in the data quality. Indeed, there is no ideal resolution appropriate for every geographical area, since it depends on the climate variability of the context considered.…”
Section: Discussionsupporting
confidence: 87%
“…Concerning Italy, it is affected by a moderate increase in the northwestern part in DJF, while no significant changes are expected in southern Italy in DJF and in the whole domain in JJA. These results confirm only partially the findings reported in [32], so a deeper analysis at higher resolution over Italy was needed and described in [33].…”
Section: Climate Projectionssupporting
confidence: 69%
“…Mountain ranges block large-scale atmospheric flow and generate orographic rainfall, which contributes to the wet bias. It is worth noting that errors in precipitation observations may contribute to these biases over the mountainous areas, as these errors increase at high altitudes (Bucchignani et al 2016).…”
Section: Climate Evaluation Of Precipitationmentioning
confidence: 99%